(untitled) - Hailperin, Max (Australia, 2007)
Intended for juniors, seniors, and first-year graduate students, Max Hailperin’s Operating Systems and Middleware: Supporting Controlled Interaction takes a modern approach to the traditional Operating Systems course. By using this innovative text, students will obtain an understanding of how contemporary operating systems and middleware work, and why they work that way. They will also gain practical skills including the ability to reason about and program concurrent computations, understand hardware/software interactions, use empirical measurement to guide design, and analyze system security.
Keywords: Middleware,Operating systems (Computers),Computer software; Development